The Ecofeminism Practice: The Women's Movement in the Documentary Film “Sangihe Melawan” - Khairiyah, Alfiatul; Muryani, Tri; Isnania, Rahma (Departemen Sosiologi Universitas Gadjah Mada, 2024)
Ecofeminism is an interrelated and holistic theory and practice. Ecology, in conjunction with discourses on women's freedom and radical democracy, constitutes one of the primary pillars of democratic confederalism, which is the development of the political paradigm in Indonesia. Ecofeminism also manifests in several areas, including the women's resistance movement against gold mining by PT Tambang Mas Sangihe (TMS) in Sangihe. This study aims to describe the representation of the women's movement in the documentary film